Fr. Antonio de Oviedo: prefecto de la misión del Darién - Pena González, Miguel Anxo, 1969- (Naturaleza y gracia: revista cuatrimestral de ciencias eclesiásticas, 2004)
This essay introduces us to the figure of the capuchin missionary Antonio de Oviedo (1601-1652), who was the first prefect of the Darien mission. This scarcely known character is important as a veteran apostolic missionary. This is what the unedited memorials and hand written letters of this missionary show. At the same time, he is singularly important because Darien was the first capuchin mission in America. This mission encountered many obstacles; the difficulty of the work as well as natural obstacles, such as the harshness of the climate, or the opposition of the Dominicans to the presence of other religious in those lands rich in gold.